Heat dissipation and heat resistance composite material, preparation method and application thereof, and battery system

By using porous aramid material and composite filler in the power battery system, the thermal dissipation and thermal composite material of the power battery is solved, and effective heat dissipation and heat barrier are achieved to ensure the safety and stability of the battery system.

CN119410344AActive Publication Date: 2025-02-11BEIJING INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411514289.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The heat generated by the power battery during charging and discharging is likely to cause abnormal temperature rise, which in turn causes accidents such as heat loss and explosion. The existing heat insulation materials can only block the transfer of heat, but cannot effectively absorb and transfer heat.

Method used

A heat-resistance composite material is used, which includes porous aramid material and composite filler filled in its holes. The composite filler is composed of thermal phase change capsules and thermal insulation materials. The thermal phase change capsules have good heat dissipation and heat absorption. The thermal insulation material coordinates heat to pass through the composite structure after the heat-conducting phase change capsule vaporization consumption.

Benefits of technology

This material can effectively absorb and block the heat generated by thermal runaway from the battery cell, solve the contradiction between heat dissipation and thermal runaway barrier of the power battery system, prevent thermal runaway propagation, and ensure that the battery system works within the normal temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410344A_ABST
    Figure CN119410344A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat-resistant materials, and particularly relates to a heat-dissipation heat-resistant composite material, a preparation method and application thereof, and a battery system. The heat dissipation and heat resistance composite material provided by the invention comprises a heat resistance material and an insulating film coating the surface of the heat resistance material, the heat-resistant material comprises a porous aramid fiber material and a composite filler filled in holes of the porous aramid fiber material; the composite filler comprises the following components in percentage by mass: 20-50% of a heat-conducting phase change capsule and 50-80% of a heat-insulating material, and the core material of the heat-conducting phase-change capsule is a heat-conducting phase-change material. The heat dissipation and heat insulation composite material provided by the invention has dual effects of heat dissipation and heat insulation, can absorb and block heat generated by the battery monomers due to thermal runaway, solves the contradiction between heat dissipation and thermal runaway blocking of a power battery system, enables the heat dissipation and thermal runaway blocking to have a synergistic effect, and effectively inhibits and delays thermal runaway propagation in the power battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heat-resistant materials, and in particular relates to a heat-dissipating and heat-resistant composite material, a preparation method and application thereof, and a battery system. Background Art

[0002] As an energy carrier, the chemical activity of power batteries increases with the increase of energy density. While the pursuit of high energy density of power batteries brings convenience, its safety hazards are becoming more and more prominent. Since the battery generates a lot of heat during the charging and discharging process, coupled with the effects of space limitations and time accumulation, it is easy to cause abnormal temperature rise of the battery. After the thermal runaway is triggered, the heat released by the local battery cells spreads to the surrounding area, which may heat the surrounding batteries and cause thermal runaway of the surrounding batteries, and eventually cause serious accidents such as fire or even explosion. Therefore, it is of great significance to carry out the safety protection design of thermal runaway of power batteries.

[0003] At present, power batteries mainly suppress the propagation of battery thermal runaway by arranging thermal insulation materials between battery cells. When a battery cell experiences thermal runaway, the heat released by the battery is confined within the battery to prevent the heat generated by thermal runaway from being transferred to adjacent batteries. However, thermal insulation materials only serve to block heat transfer and cannot effectively absorb and transfer heat. At the same time, the addition of thermal insulation materials affects the heat dissipation performance of the power battery system at normal temperature, which can easily cause uneven battery temperature distribution and pose a potential risk of thermal runaway.

[0004] The related technology provides an aerosol honeycomb panel, including a honeycomb ceramic layer and a fire extinguishing agent filled in the ceramic layer. The method aims to use the aerosol fire extinguishing agent in the honeycomb ceramic cavity to absorb the high-temperature substances ejected through the explosion-proof valve when the battery cell thermal runaway occurs, so as to prevent the high-temperature substances from falling on the surrounding batteries and catching fire. However, this method only plays the role of extinguishing the fire of local cells after the battery thermal runaway occurs, but does not control the heat transfer path of the battery, and does not play the role of heat dissipation and heat insulation in the early and middle stages of thermal runaway. Summary of the invention

[0005] The object of the present invention is to provide a heat dissipation and heat-insulating composite material, a preparation method and application thereof, and a battery system. The heat dissipation and heat-insulating composite material provided by the present invention has excellent heat dissipation and heat-insulating properties at the same time.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a heat dissipation and heat-insulating composite material, comprising a heat-insulating material and an insulating film coated on the surface of the heat-insulating material;

[0008] The heat-resistant material includes a porous aramid material and a composite filler filled in the pores of the porous aramid material; the composite filler includes 20-50% of thermal conductive phase change capsules and 50-80% of thermal insulation material in terms of mass percentage; the core material of the thermal conductive phase change capsules is a thermal conductive phase change material.

[0009] Preferably, the mass ratio of the porous aramid material to the composite filler is 20-25:1.

[0010] Preferably, the thermal insulation material comprises one or more of hollow glass microspheres, ceramic nanofiber aerogel and silica aerogel; and the particle size of the thermal insulation material is 10 to 250 μm.

[0011] Preferably, the particle size of the thermally conductive phase change capsule is 1-100 μm; the core material phase change temperature of the thermally conductive phase change capsule is 40-60°C; the wall material of the thermally conductive phase change capsule includes silicon dioxide and / or titanium dioxide; the wall thickness of the thermally conductive phase change capsule is 0.01-10 μm.

[0012] Preferably, the emulsifier includes an anionic surfactant emulsifier and / or a nonionic surfactant emulsifier; the mass of the emulsifier is 1 to 2% of the mass of the core material;

[0013] The pH of the acidic condition is 2-3; the mass ratio of the core material to the titanium source is 1:1-3.

[0014] Preferably, the density of the porous aramid material is 0.03-0.2 g / cm 3 , thickness is 2-3mm;

[0015] The holes of the porous aramid material penetrate along the thickness direction; the holes are hexagonal prism-shaped, quadrangular prism-shaped or cylindrical; the hole diameter is 1 to 4 mm.

[0016] Preferably, the insulating film comprises an aluminum-plastic film, a high-temperature nylon film or a polyimide film; and the thickness of the insulating film is 0.075 to 0.25 mm.

[0017] The present invention also provides a method for preparing the heat dissipation and heat-insulating composite material described in the above technical solution, comprising the following steps:

[0018] Mixing the thermal conductive phase change capsules and the thermal insulation material to obtain a composite filler;

[0019] Filling the composite filler into the holes of the porous aramid material to obtain a heat-resistant material;

[0020] The heat-insulating material is encapsulated with an insulating film to obtain the heat-dissipating and heat-insulating composite material.

[0021] The present invention also provides the use of the heat dissipation and heat-resistance composite material described in the above technical solution or the heat dissipation and heat-resistance composite material obtained by the preparation method described in the above technical solution in a battery system.

[0022] The present invention also provides a battery system, comprising battery cells and heat dissipation and heat-resistant composite materials arranged alternately; the heat dissipation and heat-resistant composite material is the heat dissipation and heat-resistant composite material described in the above technical solution or the heat dissipation and heat-resistant composite material obtained by the preparation method described in the above technical solution.

[0023] The present invention provides a heat dissipation and heat-resistance composite material, comprising a heat-resistance material and an insulating film coated on the surface of the heat-resistance material; the heat-resistance material comprises a porous aramid material and a composite filler filled in the pores of the porous aramid material; the composite filler comprises 20-50% of a heat-conducting phase change capsule and 50-80% of a heat-insulating material according to the mass percentage; the core material of the heat-conducting phase change capsule is a heat-conducting phase change material. In the heat dissipation and heat-resistance composite material provided by the present invention, the heat-conducting phase change capsule has good heat dissipation and heat absorption capabilities, can effectively ensure that the battery works within the normal temperature range, and greatly improves the temperature uniformity. At the same time, after the heat-conducting phase change capsule is vaporized and consumed, the heat-insulating material can cooperate with the porous aramid material to effectively prevent heat from passing through the composite structure and prevent the occurrence of a thermal runaway chain reaction. Under the dual effects of heat dissipation and heat insulation, the heat dissipation and heat-resistance composite material can absorb and block the heat generated by the battery cell due to thermal runaway, solve the contradiction between heat dissipation and thermal runaway blocking of the power battery system, so that the two can work together to effectively inhibit and delay the propagation of thermal runaway in the power battery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 This is a schematic diagram of a battery system provided by the present invention, wherein 1 is a heat dissipation and heat-resistance composite material, and 2 is a battery cell;

[0026] Figure 2 A schematic cross-sectional view of the heat dissipation and heat-insulating composite material provided by an embodiment of the present invention along the thickness direction, wherein 3 is the heat-insulating material and 5 is the insulating film;

[0027] Figure 3 This is a schematic diagram of the structure of the heat-resistant material provided in an embodiment of the present invention, wherein 3 is the heat-resistant material, 6 is the honeycomb holes of the porous aramid material, and 4 is the composite filler. DETAILED DESCRIPTION

[0028] The present invention provides a heat dissipation and heat-insulating composite material, comprising a heat-insulating material and an insulating film coated on the surface of the heat-insulating material;

[0029] The heat-resistant material includes a porous aramid material and a composite filler filled in the pores of the porous aramid material; the composite filler includes 20-50% of thermal conductive phase change capsules and 50-80% of thermal insulation material in terms of mass percentage; the core material of the thermal conductive phase change capsules is a thermal conductive phase change material.

[0030] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0031] In the present invention, the insulating film preferably includes an aluminum-plastic film, a high-temperature nylon film or a polyimide film. In a specific embodiment, the insulating film is an aluminum-plastic film; the thickness of the insulating film is preferably 0.075 to 0.25 mm. In a specific embodiment, the thickness of the insulating film can be 0.075 mm, 0.1 mm, 0.15 mm, 0.2 mm or 0.25 mm. The insulating film wraps and protects the porous aramid material and the composite filler. When the thermally conductive phase change capsules in the composite filler absorb a large amount of heat and undergo phase change, the insulating film is compressed and ruptured, releasing the vaporized thermally conductive phase change material.

[0032] According to the percentage by mass, the composite filler includes 20-50% of the thermally conductive phase change capsules. In a specific embodiment, the mass percentage of the thermally conductive phase change capsules can be 20%, 30%, 40% or 50%; the particle size of the thermally conductive phase change capsules is preferably 1-100 μm. In a specific embodiment, the particle size of the thermally conductive phase change capsules can be 10 μm, 20 μm, 35 μm, 50 μm, 80 μm or 100 μm; the core material phase change temperature of the thermally conductive phase change capsules can be 40-60 ° C. In a specific embodiment, it can be 50°C; the core material of the thermally conductive phase change capsule preferably includes one or more of paraffin, n-octadecane and n-docosane. In a specific embodiment, the core material of the thermally conductive phase change capsule can be paraffin, n-octadecane or n-docosane; the wall material preferably includes silicon dioxide and / or titanium dioxide; the wall thickness of the thermally conductive phase change capsule is preferably 0.01 to 10 μm, and in a specific embodiment, the wall thickness of the thermally conductive phase change capsule can be 1 μm, 3 μm, 4 μm, 5 μm, 8 μm or 10 μm. The microcapsule has a clear core-shell structure, and its interior is made of a thermally conductive phase change material with a high latent heat value as the core material. When the core material reaches the phase change temperature, it can quickly vaporize and absorb a large amount of heat, and release the heat to the surrounding environment. The wall material has the advantages of stable chemical properties, non-toxic and harmless, and high thermal conductivity. By coating the wall material on the surface of the internal core material, the core material can be prevented from leaking and the spherical structure can be maintained, solving the problems of instability of the thermally conductive phase change material and the risk of leakage. If the mass percentage of the thermally conductive phase change capsules is less than the above range, the required thermal conductivity and heat absorption effects cannot be obtained. Specifically, when used in high-power electric vehicles equipped with high-energy density power batteries such as NCM811, the content of thermally conductive phase change capsules in the composite filler can be greater than 40wt% to meet the higher heat dissipation requirements of the power battery system. When used in low-speed electric passenger cars, park / scenic area sightseeing cars, logistics vehicles and other electric vehicles with lower power requirements, the content of thermally conductive phase change capsules in the composite filler can be close to 20wt%, but should not be less than 20wt% to achieve basic thermal conductivity functions.

[0033] In the present invention, the method for preparing the thermally conductive phase change capsule preferably comprises the following steps:

[0034] mixing the core material, the emulsifier and the solvent to obtain a phase change emulsion;

[0035] Mixing the phase change emulsion and a titanium source or a silicon source under acidic conditions to obtain a gel precipitate;

[0036] The gel precipitate is dried to obtain the thermally conductive phase change capsule.

[0037] The present invention mixes the core material, the emulsifier and the solvent to obtain a phase change emulsion. In the present invention, the emulsifier preferably includes an anionic surfactant emulsifier and / or a nonionic surfactant emulsifier; the anionic surfactant emulsifier preferably includes sodium dodecyl sulfate and / or sodium alginate; the nonionic surfactant emulsifier is preferably an alkylphenol polyoxyethylene ether, and in a specific embodiment, the emulsifier can be sodium dodecyl sulfate, sodium alginate or an alkylphenol polyoxyethylene ether; the mass of the emulsifier is preferably 1 to 2% of the mass of the core material; the solvent is preferably deionized water or formamide, and in a specific embodiment, the solvent can be formamide; the mass volume ratio of the core material to the solvent is preferably 10 to 30. g: 100-150mL, in a specific embodiment, the mass volume ratio of the core material and the solvent can be 10g: 100mL, 10g: 150mL, 20g: 100mL, 20g: 150mL, 30g: 100mL or 30g: 150mL; the mixing method is preferably stirring; the stirring speed is preferably 200-1000rpm, in a specific embodiment, the stirring speed can be 200rpm, 600rpm or 1000rpm; the temperature is preferably 60-75℃, in a specific embodiment, the stirring temperature can be 60℃, 65℃ or 75℃; the time is preferably 1-2h. The role of the mixing is to obtain a uniform and stable phase change emulsion.

[0038] After obtaining the phase change emulsion, the present invention mixes the phase change emulsion and a titanium source under acidic conditions to obtain a gel precipitate. In the present invention, the pH of the acidic conditions is preferably 2 to 3; the reagent providing the acidic conditions is preferably sulfuric acid or hydrochloric acid. In a specific embodiment, the reagent providing the acidic conditions can be hydrochloric acid; the mass fraction of the sulfuric acid is preferably 10% to 20%; the mass fraction of the hydrochloric acid is preferably 36% to 38%; the titanium source is preferably titanyl sulfate, tetraisopropyl titanate or tetrabutyl titanate; the silicon source is preferably tetramethyl orthosilicate, sodium silicate or ethyl orthosilicate; the mass ratio of the core material to the titanium source is preferably 1:1 to 3. In a specific embodiment, the mass ratio of the core material to the tetrabutyl titanate is preferably 1:1 to 3. The mass ratio of ester can be 1:1, 1:2 or 1:3; the mixing method is preferably stirring; the stirring speed is preferably 200-1000rpm, in a specific embodiment, the stirring speed can be 200rpm, 600rpm or 1000rpm; the temperature is preferably 60-75℃, in a specific embodiment, the stirring temperature can be 60℃, 65℃ or 75℃; the present invention has no special requirements for the mixing time, as long as the mixed system is in a gel state; the mixing also includes filtering; the filtering equipment is a vacuum pump. The function of the filtering is to obtain gel precipitation.

[0039] After obtaining the gel precipitate, the present invention dries the gel precipitate to obtain the thermally conductive phase change capsule. In the present invention, the drying preferably includes washing before the drying; the washing preferably includes deionized water washing and anhydrous ethanol washing; the washing is to ensure that the final product has high purity; the drying is preferably natural drying, and the time is preferably 24 to 48 hours. In a specific embodiment, the drying time can be 24 hours, 36 hours or 48 hours.

[0040] The preparation method of the heat-conducting phase-change capsule provided by the present invention uses the heat-conducting phase-change material as the core material for encapsulation, and microencapsulates the heat-conducting phase-change material to make it into solid powder.

[0041] According to the percentage by mass, the composite filler includes 50-80% of the thermal insulation material. In a specific embodiment, the percentage by mass of the thermal insulation material can be 50%, 60%, 70% or 80%; the thermal insulation material preferably includes one or more of hollow glass microspheres, ceramic nanofiber aerogels and silica aerogels; the particle size of the thermal insulation material is preferably 10-250 μm, and in a specific embodiment, the particle size of the thermal insulation material can be 50 μm, 100 μm, 200 μm or 250 μm; when the particle size of the thermal insulation material is greater than the above range, it is also preferred to crush the thermal insulation material; the crushing equipment is preferably a high-pressure mill; the particle size of the hollow glass microspheres is preferably 10-250 μm, and in a specific embodiment, the particle size of the hollow glass microspheres can be 10 μm, 100 μm, 200 μm or 250 μm; the wall thickness is preferably 1-2 μm; the density is preferably 0.1-0.6 g / cm 3 In a specific embodiment, the density of the hollow glass microspheres can be 0.1 g / cm 3 , 0.4g / cm 3 or 0.6g / cm 3 The thermal insulation material makes up for the problem of insufficient thermal insulation performance of porous aramid materials, wherein the hollow glass microspheres are hollow spherical inorganic non-metals, and their main components include silicon dioxide, aluminum oxide and boron oxide, which have limited weight increase on the porous aramid materials.

[0042] In the present invention, the density of the porous aramid material is preferably 0.03 to 0.2 g / cm 3 In a specific embodiment, it can be 0.05g / cm3, 0.1g / cm 3 or 0.15g / cm 3; The thickness is preferably 2-3mm; The holes of the porous aramid material preferably penetrate along the thickness direction; The holes are preferably hexagonal, quadrangular or cylindrical, and in a specific embodiment, the holes can be hexagonal; The aperture of the hole is preferably 1-4mm, and in a specific embodiment, the aperture of the hole can be 1mm, 2mm, 3mm or 4mm; The mass ratio of the porous aramid material and the composite filler is preferably 20-25:1, and in a specific embodiment, the mass ratio of the porous aramid board and the composite filler can be 20:1, 22:1 or 25:1. The raw materials for preparing the porous aramid material include aramid fiber, phenolic resin, epoxy resin, polyester resin, etc., and are made through the steps of stretching, shaping, dipping, curing, etc., and have light weight, high mechanical strength, good flame retardancy and high temperature resistance.

[0043] In the heat dissipation and heat-resistance composite material provided by the present invention, in the early stage of battery thermal runaway evolution (temperature <100°C), the thermally conductive phase change capsules filled in the porous aramid material have a high thermal conductivity, which can effectively dissipate heat from the thermal runaway monomers and avoid the continuous accumulation of heat. When the temperature of the thermal runaway monomer reaches the phase change temperature of the thermally conductive phase change capsule, the phase change material can absorb a large amount of heat through the phase change process and release the heat to the surrounding environment. At the same time, after the thermally conductive phase change capsules are vaporized and consumed, the thermal insulation material can cooperate with the porous aramid material to further block the remaining heat, so that the heat generated by the thermal runaway of the battery is confined to a single battery, thereby inhibiting the propagation of thermal runaway in the power battery system. The above process realizes the dual functions of low-temperature heat conduction and high-temperature heat insulation of the heat dissipation and heat insulation composite material. Under the dual effects of heat dissipation and heat insulation, the heat dissipation and heat-resistance composite material can absorb and block the heat generated by the thermal runaway of the battery monomer, solving the contradiction between heat dissipation and thermal runaway blocking of the power battery system, so that the two can work together to effectively inhibit and delay the propagation of thermal runaway in the power battery system.

[0044] The present invention also provides a method for preparing the heat dissipation and heat-insulating composite material described in the above technical solution, comprising the following steps:

[0045] Mixing the thermal conductive phase change capsules and the thermal insulation material to obtain a composite filler;

[0046] Filling the composite filler into the holes of the porous aramid material to obtain a heat-resistant material;

[0047] The heat-insulating material is encapsulated with an insulating film to obtain the heat-dissipating and heat-insulating composite material.

[0048] The present invention mixes the thermally conductive phase change capsules and the thermal insulation material to obtain a composite filler. The present invention does not have any special restrictions on the mixing process, and the composite filler can be made uniform by using a mixing method well known to those skilled in the art.

[0049] After obtaining the composite filler, the present invention fills the composite filler into the holes of the porous aramid material to obtain a heat-resistant material. In the present invention, the filling preferably includes encapsulating one side of the porous aramid material; the encapsulation method is preferably bonding; the bonding agent is preferably structural adhesive; the filling is preferably manual filling or machine filling. The function of the single-sided encapsulation is to prevent leakage of the filled composite filler.

[0050] After obtaining the heat-resistant material, the present invention uses an insulating film to encapsulate the heat-resistant material to obtain the heat-dissipating and heat-resistant composite material. In the present invention, the encapsulation method is preferably bonding; and the bonding agent is preferably structural adhesive.

[0051] The present invention also provides the use of the heat dissipation and heat-resistance composite material described in the above technical solution or the heat dissipation and heat-resistance composite material obtained by the preparation method described in the above technical solution in a battery system.

[0052] The present invention applies the heat dissipation and heat-resistant composite material to the battery system, which can be used for heat dissipation of the power battery system and prevention of thermal runaway propagation, and significantly improves the mass energy density and volume energy density of the battery pack while ensuring the safety of the battery pack.

[0053] The present invention also provides a battery system, comprising battery cells and heat dissipation and heat-resistant composite materials arranged alternately; the heat dissipation and heat-resistant composite material is the heat dissipation and heat-resistant composite material described in the above technical solution or the heat dissipation and heat-resistant composite material obtained by the preparation method described in the above technical solution.

[0054] In order to further illustrate the present invention, the heat dissipation and heat-resistant composite material provided by the present invention, its preparation method and application, and battery system are described in detail below in combination with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0055] Figure 1 Schematic diagram of the battery system provided by the present invention, wherein 1 is a heat dissipation and heat resistance composite material, and 2 is a battery cell. Figure 1 As shown, the present invention proposes a heat dissipation and heat-resistant composite material for dissipating heat from a power battery system and preventing the spread of thermal runaway. The heat dissipation and heat-resistant composite material is tightly installed in the gap formed between adjacent battery cells. The heat dissipation and heat-resistant composite material and the battery cells are alternately arranged, and the largest side surface of the battery cell is in close contact with the working surface of the honeycomb composite structure.

[0056] Figure 2 A schematic cross-sectional view of the heat dissipation and heat-insulating composite material provided by an embodiment of the present invention along the thickness direction, wherein 3 is the heat-insulating material and 5 is the insulating film; Figure 3 This is a schematic diagram of the structure of the heat-resistant material provided by an embodiment of the present invention, wherein 3 is the heat-resistant material, 6 is the honeycomb holes of the porous aramid material, and 4 is the composite filler. Figures 2 to 3 As shown, the heat dissipation and heat-resistant composite material includes a porous aramid material, a composite filler and an insulating film. The porous aramid material is composed of a plurality of honeycomb holes arranged in a hollow hexagonal prism. According to different arrangements, the porous aramid material can be divided into meta-aramid honeycombs and para-aramid honeycombs. The appropriate core cell aperture and core material thickness can be selected according to the size of the battery cell and the thermal management requirements. Furthermore, each honeycomb hole is filled with a composite filler, and the composite filler is composed of a thermally conductive phase change capsule and a thermal insulation material. The composite filler is solid and is easy to fill and adsorb and store in the honeycomb holes. By adjusting the type and proportion of the thermally conductive phase change capsule and the thermal insulation material, the thermal conductivity and thermal insulation properties of the heat dissipation and heat-resistant composite material can be further optimized to meet the needs of different application scenarios.

[0057] Example 1

[0058] Preparation of thermal conductive phase change microcapsules: Dissolve 10g of n-docosan in 100mL of formamide, add 0.1g of sodium dodecyl sulfate to the solution, and stir at 600rpm for 1h at 75°C to obtain a uniform and stable phase change emulsion. Add 37% hydrochloric acid by mass to the reaction solution and adjust its pH to 2.5. Continue to add 10g of tetrabutyl titanate to the reaction solution and stir at 750rpm at 75°C until it becomes a gel. Filter the solution with a vacuum pump to obtain a gel precipitate, wash it with deionized water and anhydrous ethanol, and let it stand and dry for 24 hours to finally obtain a titanium dioxide-coated n-docosan microcapsule solid powder with a particle size of 50μm and a wall thickness of 5μm.

[0059] Preparation of honeycomb composite structure heat dissipation and heat insulation material: Aramid honeycomb panel with a size of 300mm×100mm×2mm and a honeycomb aperture of 3mm was selected. Hollow glass microsphere powder and n-docosane microcapsule powder with a mass ratio of 3:2 were uniformly mixed to form a composite filler. The hollow glass microsphere had a particle size of 100μm, a wall thickness of 2μm, and a density of 0.4g / cm 3 According to the size of battery cells and aramid honeycomb panels, aluminum-plastic films (thickness of 0.2 mm, 10 g) were cut to the required size; structural adhesive was used to bond the lower surface of the aramid honeycomb panel to the aluminum-plastic film at room temperature, and a piston syringe was used to fill the composite filler powder into the honeycomb, with the mass ratio of aramid honeycomb panel to filler being 22:1; after filling, the aluminum-plastic film was bonded to the upper surface of the honeycomb core material to obtain a honeycomb composite structure heat dissipation and heat-resistance material with a size of 300.4 mm × 100.4 mm × 2.4 mm.

[0060] Example 2

[0061] Preparation of thermal conductive phase change microcapsules: Dissolve 10g of paraffin in 100mL of formamide, add 0.1g of sodium dodecyl sulfate to the solution, and stir at 600rpm for 1h at 75°C to obtain a uniform and stable phase change emulsion. Add 37% hydrochloric acid by mass to the reaction solution and adjust its pH to 2.5. Continue to add 10g of tetrabutyl titanate to the reaction solution and stir at 750rpm at 75°C until it becomes a gel. Filter the solution with a vacuum pump to obtain a gel precipitate, wash it with deionized water and anhydrous ethanol, and let it stand and dry for 24 hours to finally obtain a titanium dioxide-coated paraffin microcapsule solid powder with a particle size of 50μm and a wall thickness of 5μm.

[0062] Preparation of honeycomb composite structure heat dissipation and heat insulation material: Aramid honeycomb panel with a size of 300mm×100mm×2mm and a core cell aperture of 3mm was selected. Hollow glass microsphere powder and paraffin microcapsule powder with a mass ratio of 3:2 were uniformly mixed to form a composite filler. The hollow glass microsphere had a particle size of 100μm, a wall thickness of 2μm, and a density of 0.4g / cm 3 According to the size of battery cells and aramid honeycomb panels, aluminum-plastic films (thickness of 0.2 mm, 10 g) were cut to the required size; structural adhesive was used to bond the lower surface of the aramid honeycomb panel to the aluminum-plastic film at room temperature, and a piston syringe was used to fill the composite filler powder into the honeycomb, with the mass ratio of aramid honeycomb panel to filler being 22:1; after filling, the aluminum-plastic film was bonded to the upper surface of the honeycomb core material to obtain a honeycomb composite structure heat dissipation and heat-resistance material with a size of 300.4 mm × 100.4 mm × 2.4 mm.

[0063] Comparative Example 1

[0064] The aramid honeycomb panel was selected to have a size of 300 mm×100 mm×2 mm, and an aluminum-plastic film (thickness of 0.2 mm, 10 g) was bonded to the upper surface of the aramid honeycomb panel without filling with composite fillers.

[0065] Test Case

[0066] The thermal conductivity of the materials obtained in Examples 1 to 2 and Comparative Example 1 at 25° C., 60° C. and 100° C. was tested using a thermal constant analyzer. The test results are shown in Table 1.

[0067] Table 1 Thermal conductivity of the materials obtained in Examples 1-2 and Comparative Example 1 at 25°C, 60°C and 100°C

[0068]

[0069] It can be seen from Table 1 that the honeycomb composite material proposed in the present invention has a higher thermal conductivity at room temperature, which ensures the heat dissipation performance of the power battery system at normal temperature; the thermal conductivity is 0.06W / m·K after the 100°C thermal conductive phase change material is completely consumed, which improves the thermal insulation performance of the aramid honeycomb panel and has a better effect on suppressing the heat spread of the power battery system.

[0070] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A heat dissipation and heat-insulating composite material, characterized in that: It includes a heat-resistant material and an insulating film coated on the surface of the heat-resistant material; The heat-resistant material includes a porous aramid material and a composite filler filled in the pores of the porous aramid material; the composite filler includes 20-50% of thermal conductive phase change capsules and 50-80% of thermal insulation material in terms of mass percentage; the core material of the thermal conductive phase change capsules is a thermal conductive phase change material.

2. The heat dissipation and heat-resistance composite material according to claim 1, characterized in that: The mass ratio of the porous aramid material to the composite filler is 20-25:

1.

3. The heat dissipation and heat-resistance composite material according to claim 1, characterized in that: The thermal insulation material comprises one or more of hollow glass microspheres, ceramic nanofiber aerogel and silicon dioxide aerogel; the particle size of the thermal insulation material is 10 to 250 μm.

4. The heat dissipation and heat-resistance composite material according to claim 1, characterized in that: The particle size of the thermally conductive phase change capsule is 1 to 100 μm; the phase change temperature of the core material of the thermally conductive phase change capsule is 40 to 60° C.; the wall material of the thermally conductive phase change capsule includes silicon dioxide and / or titanium dioxide; and the wall thickness of the thermally conductive phase change capsule is 0.01 to 10 μm.

5. The heat dissipation and heat-resistance composite material according to claim 4, characterized in that: The emulsifier includes an anionic surfactant emulsifier and / or a nonionic surfactant emulsifier; the mass of the emulsifier is 1 to 2% of the mass of the core material; The pH of the acidic condition is 2-3; the mass ratio of the core material to the titanium source is 1:1-3.

6. The heat dissipation and heat-insulating composite material according to claim 1 or 2, characterized in that: The density of the porous aramid material is 0.03-0.2 g / cm 3 , thickness is 2-3mm; The holes of the porous aramid material penetrate along the thickness direction; the holes are hexagonal prism-shaped, quadrangular prism-shaped or cylindrical; the hole diameter is 1 to 4 mm.

7. The heat dissipation and heat-insulating composite material according to claim 1, characterized in that: The insulating film comprises an aluminum-plastic film, a high-temperature nylon film or a polyimide film; the thickness of the insulating film is 0.075-0.25 mm.

8. The method for preparing the heat dissipating and heat-resistant composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing the thermal conductive phase change capsules and the thermal insulation material to obtain a composite filler; Filling the composite filler into the holes of the porous aramid material to obtain a heat-resistant material; The heat-insulating material is encapsulated with an insulating film to obtain the heat-dissipating and heat-insulating composite material.

9. Use of the heat dissipating and heat-insulating composite material according to any one of claims 1 to 7 or the heat dissipating and heat-insulating composite material obtained by the preparation method according to claim 8 in a battery system.

10. A battery system, characterized in that: The invention comprises battery cells and heat dissipation and heat-resistance composite materials which are arranged alternately; the heat dissipation and heat-resistance composite materials are the heat dissipation and heat-resistance composite materials according to any one of claims 1 to 7 or the heat dissipation and heat-resistance composite materials obtained by the preparation method according to claim 8.

Citation Information

Patent Citations

  • Graphene-based heat conduction silica gel phase change composite material and preparation method thereof

    CN105348797A

  • Phase change and energy storage heat-insulation material as well as preparation method and application thereof

    CN108179006A

  • Aerogel-containing phase-change energy-storage thermal-insulation board, preparation method and application thereof

    CN113400739A

  • High-thermal-conductivity semi-solid phase-change heat-insulation composite material as well as preparation method and application thereof

    CN116574488A

  • Aerogel composite material, preparation method therefor, and use thereof

    WO2024077677A1